ANALISIS TRADISI PERAYAAN AGHI AYO ONAM PADA MASYARAKAT KECAMATAN BANGKINANG - Suci Affrilla Fahrifa; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research motivated by the tradition of Aghi Ayo onam celebrations in the people of Bangkinang sub-district, which is a tradition of pride in the people of Bangkinang sub-district there are rich in religious, moral, cultural and other values. But now the tradition has many changes not only in process of its implementation, but also changes in enthusias of its people. The formulation of the problem in this research is How the Aghi Ayo Onam Tradition in the current society of Bangkinang sub-district and How the enthusiasm of the people towards Aghi Ayo Onam Tradition in Bangkinang sub-district. The purpose of this research are: to Knowing the tradition of the Aghi Ayo Onam Celebration in the people of Bangkinang sub-district and Knowing the enthusias of the people towards the Aghi Ayo Onam Tradition in Bangkinang sub-district society. Data collection techniques in this research are observation, interview and documentation. The respondents of this research were six people, are: one of ninik mamak, one of traditional kampar institution, one of cultural person, one society of Bangkinang sub-district and two nomads from Bangkinang. Data analysis techniques in this research used qualitative methods. The results in this research are changes in almost all the sequence traditions of aghi ayo onam, and the enthusias of the people at this time is changing and decreasing. There are two changes factor, are: external factors and internal factors, The external factor is the influence of other cultures and internal factors, are: new discoveries and increasing and decreasing populations.Key Words: Tradition of Aghi Ayo Onam